TRIPLE ANTITHROMBOTIC THERAPY FOR ATRIAL FBRILLATION AND CORONARY STENTS - Dusmuratova D.A. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Triple antithrombotic treatment for arterial fibrillation and coronary stents Triple treatment (TT) alludes to the concurrent utilize of an verbal anticoagulant (OAC), such as warfarin, and double antiplatelet treatment (DAPT), such as acetylsalicylic corrosive (ASA) furthermore clopidogrel. 1 The foremost common clinical sign for TT is patients with arterial fibrillation (AF) who have intense coronary disorder (ACS) or who have experienced percutaneous coronary mediation (PCI) with stent addition, which accounts for around 5% to 8% of all patients who experience [1]. There’s constrained prove to direct clinicians on endorsing TT. As such, it is diffcult to appraise the beneft of TT over DAPT or double treatment (ie, an OAC also a single antiplatelet specialist) in these patients. As anticipated, TT carries the next hazard of dying than double treatment or DAPT do. 3 Encourage, the chance of dying increments with proceeded use. 4 Owing to restricted prove and the complexity of this regimen, TT ought to as it were be endorsed after meeting with a cardiologist. Of note, the endorsing designs of cardiologists for these patients might change owing to the need of defnitive information. For case, a later investigation of antithrombotic endorsing in patients with AF after PCI inside one Canadian cardiology middle concluded that less than half of patients gotten TT and roughly one gotten non–evidence-based therapies.